Distinguishing thymoma from T-lymphoblastic leukaemia/lymphoma: a case-based evaluation. Issue 3 (22nd November 2018) - Boddu, Prajwal; Thakral, Beenu; Alhuraiji, Ahmed; Pemmaraju, Naveen; Kadia, Tapan; Ohanian, Maro; Ravandi, Farhad; Jabbour, Elias; Wierda, William; Khoury, Joseph D; Jain, Nitin
Abstract : T-lymphoblastic lymphoma and thymoma are distinct primary mediastinal neoplasms that can have similar clinical presentations and overlapping histological features. Microscopic distinction is occasionally difficult because the immature lymphocytes associated with thymoma may resemble T-lymphoblastic leukaemia/lymphoma cells, morphologically and immunohistochemically. An accurate diagnosis assumes particular importance since the treatment approaches for these two entities differ considerably. Multimodality diagnostic approaches incorporating histological, flow cytometry immunophenotypic‚ and molecular approaches are required. In this article, we describe four patients, each presenting with a mediastinal tumour in different clinicopathological settings. A detailed report of each case will follow, illustrating the challenges involved in the diagnosis in patients with these mediastinal neoplasms.